Improvement of crack tip position estimation in DIC images by image processing methods - Najat Zekriti; Fatima Majid; Hachimi Taoufik; Yassine Tounsi; Rajaa Rhanim; Ibrahim Mrani; Hassan Rhanim (Fracture and Structural Integrity)
The study presents and compares an application of two procedures to identify the crack tip location in PVC Sent samples under a uniaxial tensile test based on the image processing method.